INTEGRATING ISLAMIC MACROECONOMIC PRINCIPLES IN ANALYZING LABOR AND INFLATION AS DETERMINANTS OF INDONESIA’S INTERNATIONAL TRADE - Rozak, Abdul; Minhajuddin, Minhajuddin; Jerfiani, Dhenahi; Zainol, Fakhrul Anwar (Finansha: Journal of Sharia Financial Management, 2025)
This study examines the role of labor and inflation as Islamic macroeconomic determinants of Indonesia’s international trade during the period 2018–2022, offering an integrated empirical perspective that connects conventional trade theory with Islamic economic principles. It introduces an Islamic macroeconomic framework to assess labor and price stability as instruments of distributive justice and sustainable economic performance. Using a quantitative approach and multiple linear regression on secondary data from Statistics Indonesia and the World Bank, this study analyzes the relationship between annual export values, labor force participation, and inflation rates. The findings indicate that inflation has a statistically significant and negative effect on international trade, confirming that persistent price instability weakens export competitiveness. In contrast, labor shows a positive but statistically insignificant effect, suggesting that workforce growth has not been accompanied by proportional improvements in productivity. The regression model explains 61.4% of the variation in trade performance and is significant at the 10% level. Theoretically, the results reflect a divergence from conventional economic assumptions and underscore the relevance of Islamic macroeconomic instruments—such as justice (‘adl), equilibrium (tawazun), and welfare (maslahah)—in explaining trade dynamics. Practically, the study provides policy insights for designing Islamic macroeconomic strategies that integrate human capital development and ethical inflation management as pathways toward fair, stable, and sustainable trade. Overall, these findings contribute to the growing literature by empirically validating Islamic macroeconomic perspectives as a viable framework for strengthening economic resilience and social equity in Indonesia’s trade policy.